Experimental investigation of temperature and condensation control of photovoltaic panels - Naser Reda, M. (Institute of Electrical and Electronics Engineers Inc., 2019)
Photovoltaic (PV) panels in arid zones have the advantage of achieving high solar energy yields. However, there are two main problems that might compromise this advantage. First, the PV panel's electrical efficiency is strongly reduced by an increased daytime cell temperature. Second, during the night, the module surface temperature might undercut the dew point temperature. This results in water vapor condensation on the surface of the modules and, in combination with dust-loaded winds, mud formation on the panels. In the present study, a PVThermal (PV/T) hybrid system combined with an Underground Heat Storage system is being proposed to increase the efficiency of PV arrays especially in desert areas. During the day, the PV panel will be actively cooled, thus improving its electrical efficiency. During the night, it will be heated well above the dew point, thus preventing condensation. The results will show that the proposed system is able to resolve the two problems mentioned above. Due to the active thermal control, daytime PV efficiency could be increased by 10 and nocturnal condensation could be avoided. Â© 2019 IEEE.